Vedāntaparibhāṣā - Dharmarājādhvarīndra (Sampūrṇānanda-Saṃskr̥ta-Viśvavidyālaye, 2000)
Treatise, with Vedāntaparibhāṣāmaṇiprabhā and Vedāntaparibhāṣāśikhāmaṇi commentaries, on the epistemology of the Advaita philosophy.